Revealing the Organization of Catalytic Sequence-Defined Oligomers via Combined Molecular Dynamics Simulations and Network Analysis - Kardas, Sinan; Fossépré, Mathieu; Lemaur, Vincent; Fernandes, Antony E; Glinel, Karine; Jonas, Alain M; Surin, Mathieu (Journal of chemical information and modeling, 2022)
Similar to biological macromolecules such as DNA and proteins, the precise control over the monomer position in sequence-defined polymers is of paramount importance for tuning their structures and properties toward achieving specific functions. Here, we apply molecular network analysis on three-dimensional structures issued from molecular dynamics simulations to decipher how the chain organization of trifunctional catalytic oligomers is influenced by the oligomer sequence and the length of oligo(ethylene oxide) spacers. Our findings demonstrate that the tuning of their primary structures is crucial for favoring cooperative interactions between the catalytic units and thus higher catalytic activities. This combined approach can assist in establishing structure-property relationships, leading to a more rational design of sequence-defined catalytic oligomers via computational chemistry.